Fungsi Gordang Sambilan dalam Masyarakat Kampung Tongah Kecamatan Rao Kabupaten Pasaman Timur - Fadhila Yoelian; Syeilendra Syeilendra (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to find the function of Gordang sambilan in the wedding ceremony of the people of Tongah Village, Rao District, East Pasaman Regency. This type of research is qualitative research using a descriptive approach. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery, cameras and cellphones. The data in this study used primary data and secondary data. Data collection techniques are carried out by means of literature studies, observations, interviews and documentation. The steps of analyzing data are collecting data, describing data and inferring data. The results showed that in Tongah Village, Rao District, Pasaman Regency, there is a form of traditional art that has developed until now which is named after its supporting community as Gordang Sambilan music. The people of Tongah Village use Gordang Sambilan music for horja Godang traditional ceremonies as a function of emotional expression, entertainment function, communication function, physical reaction function, aesthetic pleasure function, symbolic representation function. Gordang sambilan music in Tongah Village can be enjoyed and used by all groups both in terms of age and in terms of social status.